2021
DOI: 10.1021/acs.analchem.1c02636
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Immunosensor for Cardiac Troponin I Detection Based on Covalent Organic Framework and Enzyme-Catalyzed Signal Amplification

Abstract: Herein, a highly sensitive electrochemical immunosensor was presented for the cardiac troponin I (cTnI) determination using a multifunctional covalent organic framework-based nanocomposite (HRP-Ab2-Au-COF) as the signal amplification probe. The spherical COF with a large surface area was synthesized in a short time by a simple solution-based method at room temperature. The good biocompatibility, low toxicity, and high stability in water of the COF guarantee its application in biosensing. Besides, its high poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…Evidence from the scientific literature has revealed that cardiac biomarkers, e.g., myoglobin, B-type natriuretic peptide, heart-type fatty acid binding protein (h-FABP), and cardiac troponin I (cTnI), can provide a rapid diagnosis of AMI. However, detection of the extremely small variations in the concentrations of these biomarkers during the onset of AMI remains challenging, which limits accurate diagnosis. Several techniques have been proposed for the analysis of AMI biomarkers including fluorescence, , chemiluminescence, photothermal biosensing, , and electrochemical detection. Among these, advanced photoelectrochemical (PEC) bioanalysis enables the fusion of photodriven electrochemical responses with various biological recognition events to monitor physiological and pathological parameters, making it a promising and burgeoning technique in life science research. Currently, developing unique signal-on sensing mechanisms is a significant research branch in PEC bioanalysis due to their reduced background signals and high sensitivity. Therefore, the development of a signal-on amplified PEC bioanalysis for AMI biomarker detection is highly desirable.…”
mentioning
confidence: 99%
“…Evidence from the scientific literature has revealed that cardiac biomarkers, e.g., myoglobin, B-type natriuretic peptide, heart-type fatty acid binding protein (h-FABP), and cardiac troponin I (cTnI), can provide a rapid diagnosis of AMI. However, detection of the extremely small variations in the concentrations of these biomarkers during the onset of AMI remains challenging, which limits accurate diagnosis. Several techniques have been proposed for the analysis of AMI biomarkers including fluorescence, , chemiluminescence, photothermal biosensing, , and electrochemical detection. Among these, advanced photoelectrochemical (PEC) bioanalysis enables the fusion of photodriven electrochemical responses with various biological recognition events to monitor physiological and pathological parameters, making it a promising and burgeoning technique in life science research. Currently, developing unique signal-on sensing mechanisms is a significant research branch in PEC bioanalysis due to their reduced background signals and high sensitivity. Therefore, the development of a signal-on amplified PEC bioanalysis for AMI biomarker detection is highly desirable.…”
mentioning
confidence: 99%
“…While there is nothing new about the technique, the performance of the HRP-H 2 O 2 -HQ technique is undeniable. Many studies have proven that the technique is reliable and can improve biosensor sensitivity due to the signal amplification by the excellent enzyme catalytic reaction of HRP [ 20 , 21 , 22 ]. A remarkable electrochemical reduction signal of benzoquinone is generated from the HRP catalyzation towards the reaction between H 2 O 2 and HQ.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, when horseradish peroxidase was incorporated as a signal amplifier, Au-modified DMTP-TAPB-COF was used to construct an enzymatic electroimmunosensor for cardiac troponin I. 771 The response current of this sensor was linearly related to the logarithmic concentration of cardiac troponin I with a wide sensitivity range from 5 pg mL −1 to 10 ng mL −1 and a low detection limit of 1.7 pg mL −1 . Glucose oxidase, hemoglobin, horseradish peroxidase, immunoglobulin G and cardiac troponin T did not interfere with the sensor, which could detect cardiac troponin I specifically in serum samples.…”
Section: Application Of Metalated Cofsmentioning
confidence: 99%